The Effect of Work-Life Balance, Organizational Culture, Career Path and Key Performance Indicator on Productivity through Employee Engagement - Faisal, Ahmad (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this literature research is expected to build hypotheses regarding the influence between variables which can later be used for further research in the scope of human resource management. The literature review research article on the effect of work-life balance, organizational culture, career path, and key performance indicators on productivity through employee engagement is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from secondary data or previous research relevant to this research and is sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Work Life Balance affects Employee Engagement; 2) Organizational Culture affects Employee Engagement; 3) Career Path affects Employee Engagement; 4) Key Performance Indicators affect Employee Engagement; 5) Work Life Balance affects Productivity; 6) Organizational Culture affects Productivity; 7) Career Path affects Productivity; 8) Key Performance Indicators affect Productivity; and 9) Employee Engagement affects Productivity.